New bird records for the island of Lombok - Johnstone, R E; van Balen, Bas; Dekker., R W. R. J. (KUKILA, 1992)
Seventeen species are recorded for the first time from the island of Lombok. Nine of these are maritime birds on passage and four are widely occurring migrant shore and land birds. Gallirallus striatus may be a local migrant, Chrysococcyx basalis is a visitor from Australia, and Anthreples malaccensis is presumed to be either a previously overlooked resident or a recent colonist. Hemiprocne longipenis, previously unrecorded from the Lesser Sundas, appears to be a recent colonist.